Meat, morals, and masculinity - Ruby, Matthew B.; Heine, Steven J. (Appetite, 2011)
Much research has demonstrated that people perceive consumers of “good,” low-fat foods as more moral, intelligent, and attractive, and perceive consumers of “bad,” high-fat foods as less intelligent, less moral, and less attractive. Little research has contrasted perceptions of omnivores and vegetarians, particularly with respect to morality and gender characteristics. In two between-subject studies, we investigated people's perceptions of others who follow omnivorous and vegetarian diets, controlling for the perceived healthiness of the diets in question. In both studies, omnivorous and vegetarian participants rated vegetarian targets as more virtuous and less masculine than omnivorous targets.